Perspectives on Educational Inclusion from a Small Sample of Autistic Pupils in Santiago, Chile - Olivia Eguiguren Istuany; Rebecca Wood (Scandinavian Journal of Disability Research, 2020)
The Chilean government has introduced significant changes across the school system to facilitate the educational inclusion of pupils with special educational needs and disabilities (SEND) via School Integration Programmes (SIPs). However, these policies have only been partially successful, with problems of stigmatisation and tokenistic inclusion reported. Meanwhile, other than through parental narratives, little information is available on the success of SIPs for pupils with SEND. In this small scale, exploratory case study based in a state school in Santiago, the views of five autistic pupils aged 10–19 were sought on their inclusion and participation in school. Using flexible, participatory methods and analysed via thematic analysis, the pupils provided important insights into their sensory issues, social and learning needs in school. Crucially in the Chilean context, they also revealed the particular impact of earthquake tremors on them. The implications of these findings for future research and educational practices are discussed.